The effects of blood flow restriction combined with resistance training on lower limb strength, muscle hypertrophy, jumping ability, and sprint speed in athletes: a systematic review and meta-analysis - Deng, Beiwang; Lin, Gesheng; Shi, Yuer; Li, Duanying; Guan, Zeyun; Liang, Chaoming; Sun, Jian (Frontiers in Physiology, 2025)
ObjectiveThis meta-analysis aims to evaluate the comparative effects of blood flow restriction resistance training (BFR-RT) versus traditional resistance training (RT) on lower limb muscle hypertrophy, maximal strength, jumping ability, and sprint performance in athletes.MethodsA comprehensive search was conducted across PubMed, Web of Science, the Cochrane Library, Embase and SPORTDiscus databases. This search identified 181 studies, of which 15 met the inclusion criteria. The quality of the studies was assessed using the Cochrane risk-of-bias tool, and data were analyzed using StataMP 17.0.ResultsThe analysis revealed that BFR-RT significantly enhanced lower limb maximal strength (ES = 0.27, 95% CI: 0.03–0.52, p = 0.031, I2 = 25%), demonstrating its effectiveness in improving strength. However, no significant differences were observed between BFR-RT and RT for lower limb muscle hypertrophy (ES = 0.17, 95% CI: -0.15–0.50, p = 0.293, I2 = 0%), jumping ability (ES = 0.25, 95% CI: -0.04 to 0.54, p = 0.091, I2 = 0%), or sprint performance (ES = −0.1, 95% CI: 0.39–0.19, p = 0.136, I2 = 0%).ConclusionThe findings suggest that while BFR-RT is effective in improving maximal strength, it does not offer additional benefits over traditional RT in terms of muscle hypertrophy, jumping ability, or sprint performance.